(Dis)Orientation In Place: Movements And Encounters Of The Pathars In Penang - Raman, Sanjeh Kumar (2023)
The Pathars in their migration to Penang during the nineteenth century, brought along their Vishwakarma techne heritage which subsequently shaped their enclaves, through ideoscapes and technoscapes that delineates their inhabitation, work and settlement. However, their migration was also into a place that was already fully ideated and built, prior to their arrival. Critical phenomenology as an episteme in this study is useful not only to exhume racial ideology in modern architecture that accompanied colonialism in Penang, but mobilizes methodological strategies to question tools of investigation to highlight voices of the Pathars which are on the margins. This study recovers the lived experiences of the Pathars in Penang through phenomenological ethnography study of their lifeworlds; the buildings and sites which support their everyday activities. The analysis of the study yields this community’s movements and encounters in their everydayness, to reveal their intimate and culturally situated experience of place and production of social space. The Pathars’ intertwinement of work and culture with place has not only enabled the production of social space for local Hindu community, but also the re-invention of what “home” can be in the face of a rapidly changing city.